The Concept of Moral Education (Comparative Study of the Book of Ayyuhal Walad by Imam Ghazali and Serat Wulangreh by Pakubuwono IV) - Tri Agus Santoso (Syntax Idea)
Microsoft Office Translator This study aims to analyze the concept of moral education in the Book of Ayyuhal Walad by Imam Ghazali and Serat Wulangreh by Pakubuwono IV, analyze the similarities and differences in the concept of moral education in the Book of Ayyuhal Walad by Imam Ghazali and Serat Wulangreh by Paku Buwono IV, analyze the concept of moral education in the Book of Ayyuhal Walad by Imam Ghazali and Serat Wulangreh by Pakubuwono IV is still relevant to Islamic education today. This type of research is literature research. The approach used in this study is a descriptive historical approach. The primary data used in this study were Kitab Ayyuhal Walad written by Imam Ghazali and Serat Wulangreh written by Pakubuwono IV. Data collection techniques with documentation. Data analysis uses descriptive analysis methods, content analysis and critical analysis. The Discussion Method uses, inductive method, deductive method and comparative method. The results of this study that: a) the source of moral education is the Qur'an, al Sunah, ijmak, qiyas, adat and anyone who gives good, b) The purpose of moral education is to practice knowledge, have a good personality and stay away from bad behavior, seek knowledge with the aim of seeking a formal diploma is not appropriate and inappropriate because it is part of the purpose of the world, c) Educational materials are dhahir and batin (heart) educational materials sourced from sharia which includes tawhid, Sufism, ubudiyah and dhauq, which dhauq cannot be achieved except by practice, d) Everyone who learns knowledge must have a teacher or murshid. A teacher or student must have good behavior or morals, have good knowledge, riyadhoh and mujahadah,